The microbiome of the sponge Aplysina caissara in two sites with different levels of anthropogenic impact - Hardoim, Cristiane C. P. [UNESP]; Hardoim, Pablo R. [UNESP]; Lôbo-Hajdu, Gisele; Custódio, Márcio R.; Thomas, Torsten (Oxford University Press (OUP), 2023)
Despite the important roles that marine sponges play in ecosystem functioning and structuring, little is known about how the sponge holobiont responds to local anthropogenic impacts. Here we assess the influence of an impacted environment (Praia Preta) on the microbial community associated with the endemic sponge Aplysina caissara in comparison to a less-impacted area (Praia do Guaecá) from the coast of São Paulo state (Brazil, southwestern Atlantic coast). We hypothesized that the local anthropogenic impacts will change the microbiome of A. caissara and that the community assembly will be driven by a different process (i.e. deterministic versus stochastic) under distinct levels of impact. The microbiome at the amplicon sequence variants level was found to be statistically distinct between sponges from the different sites, and this was also seen for the microbial communities of the surrounding seawater and sediments. Microbial communities of A. caissara from both sites were found to be assembled by deterministic processes, even though the sites presented distinct anthropogenic impacts, showing a pivotal role of the sponge host in selecting its own microbiome. Overall, this study revealed that local anthropogenic impacts altered the microbiome of A. caissara; however, assembly processes are largely determined by the sponge host.
Keywords: barcoding; community structure; deterministic and stochastic processes; local pollution; porifera; southwestern atlantic coast